Cement-based underwater non-dispersible repair material and preparation method thereof

By combining modified cement and organic reinforced emulsion, a cement-based underwater non-dispersible repair material was prepared, which solved the dispersion and adhesion problems during underwater construction, achieved a high-strength and durable repair effect, and met the long-term service requirements of underwater engineering.

CN119143456BActive Publication Date: 2025-01-14SHIJIAZHUANG TIEDAO UNIV +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411659048.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Existing underwater concrete structure repair materials are prone to dispersion and loss during underwater construction, have poor bonding performance, are difficult to construct, and lack durability and mechanical properties, making it difficult to meet the long-term service requirements of underwater engineering.

Method used

A cement-based underwater non-dispersible repair material was prepared by using modified cement, modified fly ash, and self-made organic reinforced emulsion, along with nano-silica, thickener, water-reducing agent, and defoamer. The material's stability and bonding strength are improved by forming an interpenetrating network structure through the interfacial compatibility and physical entanglement between the modified cement and the organic reinforced emulsion.

Benefits of technology

The repair material remains stable in underwater environments, with low initial dispersion, less than 5% dispersion after 24 hours, a compressive strength exceeding 45 MPa after 28 days, a flexural strength exceeding 6 MPa, a bond strength exceeding 2.5 MPa, a permeability grade greater than P12, and a chloride ion diffusion coefficient less than 2.5 × 10⁻¹² m²/s, meeting the requirements for use in harsh environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention relates to the field of cement-based building materials technology, and in particular to a cement-based underwater non-dispersible repair material and its preparation method. By using modified cement, modified fly ash and self-made organic reinforced emulsion as the main raw materials, and in combination with nano-silica, thickener, water-reducing agent and defoamer, a cement-based underwater non-dispersible repair material that can remain stable in the underwater environment and has excellent bonding and mechanical properties is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to a cement-based underwater non-dispersible repair material and a preparation method thereof. Background Art

[0002] With the rapid development of marine engineering, water conservancy engineering, port engineering, etc., a large number of concrete structures are exposed to underwater environment for a long time.

[0003] These structures mainly include important infrastructure such as docks, offshore platforms, dams, hydropower stations, and cross-sea bridges. During their service, they are subjected to various environmental factors such as water pressure, water flow erosion, and seawater corrosion.

[0004] Under the influence of this long-term and complex environment, concrete structures often suffer from defects such as cracks, holes, and spalling.

[0005] If these defects are not repaired promptly and effectively, the structural performance will continue to deteriorate, which will eventually seriously affect the safety and service life of the structure.

[0006] At present, in underwater concrete structure repair projects, commonly used repair materials mainly include traditional cement-based repair materials, epoxy resin-based repair materials, polymer-modified cement-based materials and sulphoaluminate cement-based repair materials.

[0007] Although traditional cement-based repair materials have the advantages of good compatibility with the substrate and low cost, they are prone to dispersion during underwater construction, resulting in serious material loss and unsatisfactory repair effects.

[0008] Although epoxy resin-based repair materials have good bonding properties and high strength, they are difficult to construct in underwater environments, have a long curing time, and are expensive, making them difficult to promote and apply on a large scale.

[0009] Polymer-modified cement-based materials have improved the performance of cement-based materials to a certain extent, but their underwater construction performance and durability still need to be further improved.

[0010] Although sulphoaluminate cement-based repair materials have the characteristics of rapid solidification and high early strength, they have problems such as large shrinkage, high cost and poor durability.

[0011] These existing repair materials have exposed many technical problems in practical applications: during underwater construction, the materials are prone to dispersion and loss, which not only causes material waste, but also affects the quality and effect of the repair; due to the presence of moisture, the bonding performance of the material to the moist substrate is poor, the interface bonding strength is low, and the repair layer is prone to peeling; the fluidity and curing speed of the material are difficult to control, the construction operability is poor, the time window is short, and the process is complicated; the durability and mechanical properties after repair often cannot meet the engineering requirements, the strength development is not ideal, the water resistance and impermeability are insufficient, and it is difficult to adapt to long-term service requirements. Summary of the invention

[0012] In order to solve the problems existing in the prior art, the present invention provides a cement-based underwater non-dispersible repair material and a preparation method thereof. By adopting modified cement, modified fly ash and homemade organic reinforcing emulsion as main raw materials, and in combination with the use of nano-silicon dioxide, a thickener, a water reducer and a defoaming agent, a cement-based underwater non-dispersible repair material is prepared, which can maintain a stable existence in an underwater environment and has excellent bonding properties and mechanical properties.

[0013] Specifically, the cement-based underwater non-dispersible repair material of the present invention is composed of the following raw materials in parts by weight:

[0014] 100 parts of modified cement, 30-40 parts of modified fly ash, 15-20 parts of organic reinforced emulsion, 2-5 parts of nano silicon dioxide, 0.8-1.2 parts of thickener, 1-2 parts of water reducer, 0.3-0.5 parts of defoamer, and 25-30 parts of water.

[0015] Preferably, the modified cement preparation process is: mixing cement, coupling agent, and phosphorus slag powder in a mass ratio of 100:(2-4):(3-6), and stirring at high speed to obtain the modified cement.

[0016] Preferably, the modified fly ash preparation process is: fly ash and octadecyltrimethoxysilane are mixed in a mass ratio of 35:(1-3), and stirred at high speed to obtain the modified fly ash.

[0017] Preferably, the preparation process of the organic enhanced emulsion is: heat and stir 100-110 parts of isophorone diisocyanate, 110-120 parts of polyether diol, 13-16 parts of dimethylhydroxypropionic acid, and 0.1-0.3 parts of dibutyltin dilaurate, add 8-11 parts of 1,4-butanediol, continue stirring, cool, add 7-9 parts of triethylamine, stir again, slowly add 390-405 parts of deionized water and stir at high speed to obtain the product.

[0018] The invention adopts modified cement, modified fly ash and organic reinforced emulsion as main components, wherein fly ash is modified by octadecyl trimethoxysilane to effectively reduce its water dispersibility and provide underwater stability; the organic reinforced emulsion selects isophorone diisocyanate as the main chain rigid unit, introduces polyether diol to provide a flexible segment, and introduces a hydrophilic group by using dimethyl hydroxypropionic acid; the cement is modified by a coupling agent and phosphorus slag powder, which can significantly improve the interface compatibility between cement and organic reinforced emulsion and provide the overall bonding strength of the repair material; during the hydration process of the organic reinforced emulsion, the NCO terminal group is partially hydrolyzed and reacts with Ca in the cement. 2+ Complexation occurs, and a hydrogen bond network structure is formed between the molecular chains. The carboxyl groups introduced by dimethylhydroxypropionic acid react with the Ca in the cement hydration product. 2+ The modified fly ash and the hydration products of the modified cement and the hydration network of the organic reinforcing emulsion form an interpenetrating network structure through physical entanglement and chemical bonding, which significantly improves the overall performance of the material. The phosphorus slag powder has a certain hydration activity in the preparation process of the modified cement, and it can regulate the hydration process of cement, fly ash particles and nano-silica to ensure the later strength of the repair material. After the phosphorus slag powder and cement are modified together, the underwater non-dispersible characteristics of the slurry can be further improved to avoid the loss of the reinforcing effect of the organic reinforcing emulsion caused by the asynchronous hydration of nano-silica.

[0019] Preferably, the cement is at least one of ordinary Portland cement and Portland cement. More preferably, the strength grade of the cement is greater than or equal to 42.5.

[0020] Preferably, the coupling agent is a silane coupling agent. More preferably, the coupling agent is KH550.

[0021] Preferably, the fly ash is secondary fly ash.

[0022] Preferably, the thickener is cellulose ether.

[0023] More preferably, the thickener is at least one of hydroxypropyl methylcellulose ether and hydroxyethyl cellulose ether.

[0024] Preferably, the water reducer is a polycarboxylate water reducer.

[0025] Preferably, the defoamer is a silicone defoamer.

[0026] Preferably, in the modified cement preparation process, the mixing temperature is 60-70° C. A high temperature environment is conducive to the reaction, but is not limited to the temperature of the present invention.

[0027] Preferably, in the modified fly ash preparation process, the mixing temperature is 50-60° C. A high temperature environment is conducive to the reaction, but is not limited to the temperature of the present invention.

[0028] Preferably, in the process for preparing the organic enhanced emulsion, the temperature is raised to 85-90° C. and stirred for 2-2.5 hours, the stirring time is continued for 1-1.5 hours, the temperature is lowered to 58-60° C., the stirring time is again for 0.5-1 hour, and the high-speed stirring time is 15-20 minutes.

[0029] The present invention also relates to a method for preparing the above-mentioned cement-based underwater non-dispersible repair material, which specifically comprises the following steps:

[0030] 1) Weigh each raw material by weight,

[0031] 2) Mix modified cement, modified fly ash and nano-silicon dioxide evenly to obtain dry material.

[0032] 3) Evenly mix the organic enhanced emulsion, thickener, water reducer, defoamer and water to obtain a liquid material.

[0033] 4) Mix the liquid and dry materials evenly to obtain slurry.

[0034] 5) Use the slurry for underwater repair construction.

[0035] The repair material of the present invention can not only maintain a stable existence in an underwater environment, but also has excellent bonding properties and mechanical properties. That is, the repair material of the present invention not only has good underwater non-dispersibility and construction performance, but can also form an effective interface bonding with a moist substrate, and at the same time has appropriate curing characteristics and excellent durability. This has important engineering value and practical significance for ensuring the safe operation of underwater engineering facilities and extending their service life.

[0036] The repair material prepared by the invention exhibits excellent comprehensive performance.

[0037] The repair material has outstanding non-dispersion performance in underwater environment, with an initial dispersion rate of less than 3% and a 24-hour dispersion rate of less than 5%, which is significantly better than the existing technical level.

[0038] The repair material has excellent mechanical properties, with a 28-day compressive strength exceeding 45MPa, a flexural strength exceeding 6MPa, and a bonding strength with the substrate exceeding 2.5MPa.

[0039] In terms of durability, the impermeability grade of the repair material is greater than P12, and the chloride ion diffusion coefficient is less than 2.5×10 -12 m² / s, fully meeting the requirements for use in harsh environments.

[0040] At the same time, the repair material also has good construction performance, sufficient operating time, moderate early strength and simple and easy construction technology. DETAILED DESCRIPTION

[0041] In order to characterize the technical effect of the present invention, a repair material was prepared and its performance was tested.

[0042] During the test, P·O42.5 cement was used as cement, KH550 as coupling agent, secondary fly ash as fly ash, hydroxypropyl methyl cellulose ether as thickener, polycarboxylic acid water reducer as water reducer, and silicone defoamer as defoamer.

[0043] During the test, the slurry dispersion rate is tested underwater. During the molding process, the slurry is poured into a mold placed underwater to be molded to test the compressive and flexural strengths. The slurry is also poured into a mold paved with hardened cement specimens to be molded to test the bonding strength. The specimen curing is also carried out in an underwater immersion environment.

[0044] Example 1

[0045] The repair material is characterized by being composed of the following raw materials in parts by weight:

[0046] 100 parts of modified cement, 40 parts of modified fly ash, 16 parts of organic reinforced emulsion, 5 parts of nano silicon dioxide, 1 part of thickener, 2 parts of water reducer, 0.3 parts of defoamer, 28 parts of water,

[0047] The modified cement preparation process is as follows: cement, coupling agent and phosphorus slag powder are mixed in a mass ratio of 100:3:5 and stirred at high speed to obtain the modified cement.

[0048] The modified fly ash preparation process is as follows: fly ash and octadecyl trimethoxy silane are mixed in a mass ratio of 35:2, and stirred at high speed to obtain:

[0049] The organic enhanced emulsion preparation process is as follows: 100 parts of isophorone diisocyanate, 110 parts of polyether diol, 16 parts of dimethylhydroxypropionic acid, and 0.2 parts of dibutyltin dilaurate are heated and stirred, 10 parts of 1,4-butanediol are added, stirring is continued, the temperature is lowered, 9 parts of triethylamine are added, stirring is repeated, and 400 parts of deionized water are slowly added and stirred at high speed to obtain the organic enhanced emulsion.

[0050] After testing, the initial dispersion rate of the slurry was 2.5%, the dispersion rate after 24 hours was 4.2%, the compressive strength after 28 days was 48.5 MPa, the flexural strength after 28 days was 6.8 MPa, the bonding strength after 28 days was 2.8 MPa, the impermeability grade was P14, and the chloride ion diffusion coefficient was 2.1×10 -12 m² / s.

[0051] Example 2

[0052] The repair material is characterized by being composed of the following raw materials in parts by weight:

[0053] 100 parts of modified cement, 35 parts of modified fly ash, 20 parts of organic reinforced emulsion, 4 parts of nano silicon dioxide, 0.9 parts of thickener, 1.8 parts of water reducer, 0.4 parts of defoamer, 28 parts of water,

[0054] The modified cement preparation process is as follows: cement, coupling agent and phosphorus slag powder are mixed in a mass ratio of 100:4:6 and stirred at high speed to obtain the modified cement.

[0055] The modified fly ash preparation process is as follows: fly ash and octadecyl trimethoxy silane are mixed in a mass ratio of 35:2.5, and stirred at high speed to obtain:

[0056] The organic enhanced emulsion preparation process is as follows: 110 parts of isophorone diisocyanate, 115 parts of polyether diol, 14 parts of dimethylhydroxypropionic acid, and 0.2 parts of dibutyltin dilaurate are heated and stirred, 10 parts of 1,4-butanediol are added, stirring is continued, the temperature is lowered, 7 parts of triethylamine are added, stirring is repeated, and 400 parts of deionized water are slowly added and stirred at high speed to obtain the organic enhanced emulsion.

[0057] After testing, the initial dispersion rate of the slurry was 2.7%, the dispersion rate after 24 hours was 4.4%, the compressive strength after 28 days was 46.9 MPa, the flexural strength after 28 days was 6.5 MPa, the bonding strength after 28 days was 2.6 MPa, the impermeability grade was P14, and the chloride ion diffusion coefficient was 2.3×10 -12 m² / s.

[0058] Comparative Example 1

[0059] The repair material is characterized by being composed of the following raw materials in parts by weight:

[0060] PO42.5 cement 100 parts, modified fly ash 40 parts, organic reinforced emulsion 16 parts, nano silicon dioxide 5 parts, thickener 1 part, water reducer 2 parts, defoamer 0.3 parts, water 28 parts,

[0061] The modified fly ash preparation process is as follows: fly ash and octadecyl trimethoxy silane are mixed in a mass ratio of 35:2, and stirred at high speed to obtain:

[0062] The organic enhanced emulsion preparation process is as follows: 100 parts of isophorone diisocyanate, 110 parts of polyether diol, 16 parts of dimethylhydroxypropionic acid, and 0.2 parts of dibutyltin dilaurate are heated and stirred, 10 parts of 1,4-butanediol are added, stirring is continued, the temperature is lowered, 9 parts of triethylamine are added, stirring is repeated, and 400 parts of deionized water are slowly added and stirred at high speed to obtain the organic enhanced emulsion.

[0063] After testing, the initial dispersion rate of the slurry was 3.7%, the dispersion rate after 24 hours was 7.6%, the compressive strength after 28 days was 44.0 MPa, the flexural strength after 28 days was 3.9 MPa, the bonding strength after 28 days was 2.0 MPa, the impermeability grade was P12, and the chloride ion diffusion coefficient was 2.8×10 -12 m² / s.

[0064] Comparative Example 2

[0065] The repair material is characterized by being composed of the following raw materials in parts by weight:

[0066] 100 parts of modified cement, 40 parts of secondary fly ash, 16 parts of organic reinforced emulsion, 5 parts of nano silicon dioxide, 1 part of thickener, 2 parts of water reducer, 0.3 parts of defoamer, 28 parts of water,

[0067] The modified cement preparation process is as follows: cement, coupling agent and phosphorus slag powder are mixed in a mass ratio of 100:3:5 and stirred at high speed to obtain the modified cement.

[0068] The organic enhanced emulsion preparation process is as follows: 100 parts of isophorone diisocyanate, 110 parts of polyether diol, 16 parts of dimethylhydroxypropionic acid, and 0.2 parts of dibutyltin dilaurate are heated and stirred, 10 parts of 1,4-butanediol are added, stirring is continued, the temperature is lowered, 9 parts of triethylamine are added, stirring is repeated, and 400 parts of deionized water are slowly added and stirred at high speed to obtain the organic enhanced emulsion.

[0069] After testing, the initial dispersion rate of the slurry was 7.3%, the dispersion rate after 24 hours was 15.2%, the compressive strength after 28 days was 41.6 MPa, the flexural strength after 28 days was 3.7 MPa, the bonding strength after 28 days was 1.9 MPa, the impermeability grade was P10, and the chloride ion diffusion coefficient was 3.4×10 -12 m² / s.

[0070] Comparative Example 3

[0071] The repair material is characterized by being composed of the following raw materials in parts by weight:

[0072] PO42.5 cement 100 parts, secondary fly ash 40 parts, organic reinforced emulsion 16 parts, nano silicon dioxide 5 parts, thickener 1 part, water reducer 2 parts, defoamer 0.3 parts, water 28 parts,

[0073] The organic enhanced emulsion preparation process is as follows: 100 parts of isophorone diisocyanate, 110 parts of polyether diol, 16 parts of dimethylhydroxypropionic acid, and 0.2 parts of dibutyltin dilaurate are heated and stirred, 10 parts of 1,4-butanediol are added, stirring is continued, the temperature is lowered, 9 parts of triethylamine are added, stirring is repeated, and 400 parts of deionized water are slowly added and stirred at high speed to obtain the organic enhanced emulsion.

[0074] After testing, the initial dispersion rate of the slurry was 15.8%, the dispersion rate after 24 hours was 22.5%, the compressive strength after 28 days was 32.6 MPa, the flexural strength after 28 days was 3.1 MPa, the bonding strength after 28 days was 1.1 MPa, the impermeability grade was P8, and the chloride ion diffusion coefficient was 5.7×10 -12 m² / s.

[0075] Comparative Example 4

[0076] The repair material is characterized by being composed of the following raw materials in parts by weight:

[0077] 100 parts of modified cement, 40 parts of modified fly ash, 16 parts of acrylic emulsion, 5 parts of nano silicon dioxide, 1 part of thickener, 2 parts of water reducer, 0.3 parts of defoamer, 28 parts of water,

[0078] The modified cement preparation process is as follows: cement, coupling agent and phosphorus slag powder are mixed in a mass ratio of 100:3:5 and stirred at high speed to obtain the modified cement.

[0079] The modified fly ash preparation process is as follows: fly ash and octadecyltrimethoxysilane are mixed in a mass ratio of 35:2, and stirred at high speed to obtain the modified fly ash.

[0080] After testing, the initial dispersion rate of the slurry was 8.8%, the dispersion rate after 24 hours was 15.3%, the compressive strength after 28 days was 37.0 MPa, the flexural strength after 28 days was 3.3 MPa, the bonding strength after 28 days was 1.5 MPa, the impermeability grade was P10, and the chloride ion diffusion coefficient was 4.2×10 -12 m² / s.

[0081] Comparative Example 5

[0082] The repair material is characterized by being composed of the following raw materials in parts by weight:

[0083] 100 parts of modified cement, 40 parts of modified fly ash, 16 parts of organic reinforced emulsion, 5 parts of nano silicon dioxide, 1 part of thickener, 2 parts of water reducer, 0.3 parts of defoamer, 28 parts of water,

[0084] The modified cement preparation process is as follows: cement and coupling agent are mixed in a mass ratio of 100:3 and stirred at high speed to obtain the modified cement.

[0085] The modified fly ash preparation process is as follows: fly ash and octadecyl trimethoxy silane are mixed in a mass ratio of 35:2, and stirred at high speed to obtain:

[0086] The organic enhanced emulsion preparation process is as follows: 100 parts of 4,4'-dicyclohexylmethane diisocyanate, 110 parts of polyether diol, 16 parts of dimethylhydroxypropionic acid, and 0.2 parts of dibutyltin dilaurate are heated and stirred, 10 parts of 1,4-butanediol are added, stirring is continued, the temperature is lowered, 9 parts of triethylamine are added, stirring is repeated, and 400 parts of deionized water are slowly added and stirred at high speed to obtain the organic enhanced emulsion.

[0087] After testing, the initial dispersion rate of the slurry was 7.2%, the dispersion rate after 24 hours was 13.9%, the compressive strength after 28 days was 39.3 MPa, the flexural strength after 28 days was 3.1 MPa, the bonding strength after 28 days was 1.6 MPa, the impermeability grade was P10, and the chloride ion diffusion coefficient was 3.8×10 -12 m² / s.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cement-based underwater non-dispersible repair material, characterized in that: It is composed of the following raw materials in parts by weight: 100 parts of modified cement, 30-40 parts of modified fly ash, 15-20 parts of organic reinforced emulsion, 2-5 parts of nano silicon dioxide, 0.8-1.2 parts of thickener, 1-2 parts of water reducer, 0.3-0.5 parts of defoamer, 25-30 parts of water, The modified cement preparation process is as follows: cement, coupling agent and phosphorus slag powder are mixed in a mass ratio of 100:(2-4):(3-6), and stirred at high speed to obtain the modified cement. The modified fly ash preparation process is as follows: fly ash and octadecyl trimethoxy silane are mixed in a mass ratio of 35:(1-3), and stirred at high speed to obtain: The organic enhanced emulsion preparation process comprises: heating and stirring 100-110 parts of isophorone diisocyanate, 110-120 parts of polyether diol, 13-16 parts of dimethylhydroxypropionic acid and 0.1-0.3 parts of dibutyltin dilaurate, adding 8-11 parts of 1,4-butanediol, continuing stirring, cooling, adding 7-9 parts of triethylamine, stirring again, slowly adding 390-405 parts of deionized water and stirring at high speed to obtain the organic enhanced emulsion.

2. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: The cement is at least one of ordinary Portland cement and Portland cement.

3. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: The fly ash is secondary fly ash.

4. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: The thickener is cellulose ether.

5. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

6. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: The defoamer is an organosilicon defoamer.

7. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: In the modified cement preparation process, the mixing temperature is 60-70°C.

8. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: In the modified fly ash preparation process, the mixing temperature is 50-60°C.

9. The cement-based underwater non-dispersible repair material according to claim 1, characterized in that: In the process for preparing the organic enhanced emulsion, the temperature is raised to 85-90° C. and stirred for 2-2.5 hours, the stirring time is continued for 1-1.5 hours, the temperature is lowered to 58-60° C., the stirring time is again for 0.5-1 hour, and the high-speed stirring time is 15-20 minutes.

10. The method for preparing the cement-based underwater non-dispersible repair material according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Mix the modified cement, modified fly ash and nano-silicon dioxide evenly to obtain dry material. 3) Evenly mix the organic enhanced emulsion, thickener, water reducer, defoamer and water to obtain a liquid material. 4) Mix the liquid and dry materials evenly to obtain slurry. 5) Use the slurry for underwater repair construction.

Citation Information

Patent Citations

  • Hydrophobic foam concrete and preparation method thereof

    CN111333394A

  • Concrete admixture and preparation method thereof

    CN115073047A